Quantification of the Stress to which West Bengal Forests are Subjected - Sarkar, S. K (Indian Forester, 1998)
Due to biotic pressure , the West Bengal forests are under tremendous stress which caused rapid degradation of the forests during last few decades. In this article an attempt has been made to quantify the stresses , which mostly go unrecorded and unnoticed , in both physical and financial terms , to highlight the severity of the problem.